Radioimmunotherapy (90Y‐Ibritumomab Tiuxetan) for Posttransplant Lymphoproliferative Disorders After Prior Exposure to Rituximab. Issue 7 (13th April 2015) - Rossignol, J.; Terriou, L.; Robu, D.; Willekens, C.; Hivert, B.; Pascal, L.; Guieze, R.; Trappe, R.; Baillet, C.; Huglo, D.; Morschhauser, F.
<x xml:space="preserve">Abstract</x> Posttransplantation lymphoproliferative disorders (PTLDs) are life‐threatening complications after solid organ and hematopoietic stem cell transplantation. Only half of CD20‐positive PTLDs respond to rituximab monotherapy, and outcomes remain poor for patients with relapsed/refractory disease, especially those who do not qualify for an anthracycline containing regimen due to frailty or comorbidities. Radioimmunotherapy (RIT) might be an option in this particular setting. We report a panel of eight patients with rituximab refractory/relapsed CD20‐positive PTLDs including three ineligible for subsequent CHOP‐like chemotherapy who received 90Y‐Ibritumomab tiuxetan as a single agent (n = 7) or combined to chemotherapy (n = 1). Five out of eight patients were kidney transplant recipients, while 2/8 had a liver transplant and 1/8 had a heart transplant. Patients received a median of two previous therapies. Overall response rate was 62.5%. Importantly, all responders achieved complete response. At a median follow‐up of 37 months [5; 84], complete response was ongoing in four patients. Toxicity was predominantly hematological and easily manageable. No graft rejection was noticed concomitantly or following RIT administration despite immunosuppression reduction after diagnosis of PTLDs. This report emphasizes the potential efficiency of salvage RIT for early rituximab refractory PTLDs without any unexpected toxicity.